The (im)possibilities of disaster risk reduction in the context of high-intensity conflict: the case of Afghanistan. (15th March 2021) - Mena, Rodrigo; Hilhorst, Dorothea
ABSTRACT: Conflict aggravates disaster risk and impact through increased vulnerability and weakened response capacities. Disaster risk reduction (DRR) and disaster governance are needed – but often deemed unfeasible – in conflict-affected areas. In Afghanistan, despite the high-intensity conflict (HIC), there is a growing body of practice on DRR. To provide insight on DRR in HIC contexts, this study used document analysis, stakeholder interviews, and participant observation to analyse the promotion, implementation, and challenges of DRR in Afghanistan. The findings show that DRR was promoted after international recognition of Afghanistan's high disaster risk, which coincided with expanding opportunities for development. Early Afghan DRR projects were hazard-oriented and focused on mitigation infrastructure, but some have shifted towards an integrated approach. DRR is challenging in HIC contexts because of complex logistical and funding needs required to overcome access and security issues. The Afghan experience shows that DRR is possible in HIC countries, provided that different levels of conflict are acknowledged, sufficient time and funding are available, and disaster governance arrangements are in place. Expectations regarding the possibilities for DRR in HIC areas should be tempered by the realities of limitations in terms of geographical coverage, real impact, and capacities to reduce vulnerability in an integrated way.